2015
DOI: 10.1007/s00221-014-4184-6
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of implicit learning of task-irrelevant Chinese tonal sequence

Abstract: The present study sought to investigate the neural basis of implicit learning of task-irrelevant perceptual sequence. A novel SRT task, the serial syllable identification task (SSI task), was used in which the participants were asked to recognize which one of two Chinese syllables was presented. The tones of the syllables were irrelevant to the task but followed an underlying structured sequence. Participants were scanned while they performed the SSI task. Results showed that, at the behavioral level, faster R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Ling et al. (2015) did not find any difference in the time course of BG and H activation (both emerging after about 8 minutes), and Turk‐Browne et al. (2009) found a slightly delayed hippocampal response (after 48 seconds compared to 32 seconds for caudate).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ling et al. (2015) did not find any difference in the time course of BG and H activation (both emerging after about 8 minutes), and Turk‐Browne et al. (2009) found a slightly delayed hippocampal response (after 48 seconds compared to 32 seconds for caudate).…”
Section: Discussionmentioning
confidence: 98%
“…Ling et al. (2015) examined learning of a sequence of Chinese tones (in Chinese native speakers) and found learning‐related activity in bilateral H, right caudate nucleus, and left superior parietal lobule. Jablonowski, Taesler, Fu, and Rose (2018) examined perceptual sequence learning of tones and found very precise learning related changes in bilateral H. Both studies used stringent tests to exclude any participants with sequence awareness.…”
Section: Sequence Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have argued that implicit learning does not always require attentional resources (Baker et al, 2004;Brosowsky et al, 2021;Jiang & Chun, 2001;Turk-Browne et al, 2008), a growing body of evidence suggests that at least some attentional resources must be available for successful implicit learning (e.g., Emberson et al, 2011;Ling et al, 2015;Riedel & Burton, 2006;Schneider et al, 2022;Toro et al, 2005). Toro et al (2005) found that in a speech statistical learning THE ROLE OF A BRIEF PRE-EXPOSURE IN IMPLICIT LEARNING 30 (SL) task, participants could successfully extract words in a recognition test after exposure by passive listening to the speech stream without other concurrent tasks.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the hippocampus plays a crucial role in reasoning regarding task uncertainty by moderating bias in information representation and the superior parietal lobule expectations (Rigoli et al, 2019). Similarly, the left hippocampus is engaged in guessing, along with the left superior parietal lobule, required for implicit perception learning (Ling et al, 2015).…”
Section: Discussionmentioning
confidence: 99%